Ambiguities in the regulation of the National Cultural System: contrast between before and after Law no. 14,835/2024 (Revista do Tribunal Regional Federal da 3ª Região, 2024)
The work addresses the historical process of implementing cultural policy for the formation of the National Culture System (SNC) and systemic repercussions arising from the cooperative federalism adopted by Brazil after the promulgation of the Federal Constitution of 1988, which inaugurates the normative aspect of the system and demands a framework own legislation, materialized by Constitutional Amendment no. 71, of 2012, which added art. 216-A to the constitutional text. The aforementioned constitutional provision only came to be regulated in 2024, through Law No. 14,835. However, even before such regulation, the federal cultural body (Ministry or Secretariat) already disciplined the SNC through infra-legal norms. In this scenario, the objective of this study is to compare the regulation of the SNC in the moments that precede and follow the legal framework of 2024. Through bibliographical and documentary research, with descriptive purposes and a deductive method, with a quantitative-qualitative approach, it is clear that the The legislator gave preference to the regulatory practices he had been practicing for a decade, despite some of them not being compatible with the constitutional provisions relating to the National Culture System.
Keywords: cultural rights; National System of Culture; EC 71/2012; fundamental rights; public policy; Law no. 14,835/2024